2012
DOI: 10.1080/10810730.2011.579688
|View full text |Cite
|
Sign up to set email alerts
|

Men's Use of an Internet-Based Decision Aid for Prostate Cancer Screening

Abstract: Most medical organizations recommend informed decision making before undergoing prostate cancer screening. The authors conducted a detailed evaluation of men's use of an interactive, Web-based prostate cancer screening decision aid. Participants (N = 531) were 57 years old (SD = 6.8), 37% were African American, and 92% had Internet access. Men completed 2 telephone interviews, pre- and 1-month post-Web site availability. Half of the sample (n = 256) accessed the Web site. Multivariate analysis revealed that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 47 publications
0
29
1
Order By: Relevance
“…In a prior analysis of our PCa screening website [29], we presented the number of unique logins, total and average time spent on particular sections of the website, use of video testimonials, and the characteristics of website users vs. nonusers. Men responded favorably to the website, spending a median of 34 min on the website, and over 88 % of users responded to all 10 values clarification items [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prior analysis of our PCa screening website [29], we presented the number of unique logins, total and average time spent on particular sections of the website, use of video testimonials, and the characteristics of website users vs. nonusers. Men responded favorably to the website, spending a median of 34 min on the website, and over 88 % of users responded to all 10 values clarification items [29].…”
Section: Introductionmentioning
confidence: 99%
“…Men responded favorably to the website, spending a median of 34 min on the website, and over 88 % of users responded to all 10 values clarification items [29]. In the current study, we assessed the degree to which our web-based decision aid impacted important decision-making outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The primary study limitation was the necessary reliance on participants' self-reported use of the decision aids. In the web arm, we compared the self-report data with the results from the tracking software and found some overestimation of decision aid use, 19 suggesting the possibility that both arms may have overestimated their use of the decision tools. However, we are unaware of any reason to expect that the degree of overestimation would differ between groups.…”
Section: Discussionmentioning
confidence: 99%
“…More information about the decision aids is available. 18,19 Measures Descriptive Variables. We assessed demographics (age, race, education level, employment, income, whether men had a regular physician, insurance, and numeracy 20 ) and clinical characteristics (comorbidities, personal history of cancer, family history of prostate cancer, prostate cancer screening history in one's lifetime and in the year prior to trial enrollment), and recollection of a prior discussion of prostate cancer screening with a physician.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation